Allergy to Uncommon Pets: New Allergies but the Same Allergens - Diaz-Perales, Araceli; González-de-Olano, David; Perez-Gordo, Marina; PASTOR-VARGAS, CARLOS (Frontiers in Immunology, 2013)
The prevalence of exotic pet allergies has been increasing over the last decade. Years ago, the main allergy-causing domestic animals were dogs and cats, although nowadays there is an increasing number of allergic diseases related to insects, rodents, amphibians, fish, and birds, among others. The current socio-economic situation, in which more and more people have to live in small apartments, might be related to this tendency. The main allergic symptoms related to exotic pets are the same as those described for dog and cat allergy: respiratory symptoms. Animal allergens are therefore, important sensitizing agents and an important risk factor for asthma. There are 3 main protein families implicated in these allergies, which are the lipocalin superfamily, serum albumin family, and secretoglobin superfamily. Detailed knowledge of the characteristics of allergens is crucial to improvement treatment of uncommon-pet allergies.